Διερεύνηση βελτιωτικών μέτρων για την ενεργειακή αναβάθμιση υφιστάμενου κτιρίου - Πέτρου, Ελένη (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
The increased energy consumption that is attributed on the building section has led to taking several measures, after the European Union direction (2010/31/EU), one of which is the improvement of the energy efficiency of the existing constructions. The present study aims to the improvement of the energy efficiency of three apartments that belong to an existing apartment building. The calculation of the energy efficiency has been done using the national software SBEMcy and following the instructions and methodology defined by the Energy Service. After the low energy classification of all three apartments, hypothetical improvement energy efficiency scenarios are following, which have next been connected between them. The hypothetical scenarios concerned the heat insulation of the apartments, application of photovoltaic and replacement of the current glazing with better quality ones than the current. The graduation study is being divided into 6 chapters of which the first two are theoretical and concern the heat transfer and the thermal insulation. The third chapter includes researches that have been done and are linked with the subject of the current graduation study. At the fourth chapter the methodology followed is being presented and at the fifth the results are being analyzed. The sixth chapter presents the suggestions-proposals for the situation improvement and the new arising results are being analyzed. At the end of the study the arising conclusions are presented. The results have shown that the placement of photovoltaic is necessary in order for all three apartments to be classified in the second category of energy efficiency. Furthermore the cost of the initial investment of any of the recommended scenarios, which have been approximately calculated, is quite high so there is need for new insulation techniques in Cyprus which will be more economical and at the same time to introduce the use of renewable energy sources. Some weaknesses in the specific edition of the used software (ISBEM-CY_3.3.d) have also been observed which concern its function and the results that it extracts, and possible applicable improvements have been proposed.
Keywords: Thermal insulation; Energy performance of buildings; Θερμομόνωση; Ενεργειακή απόδοση κτιρίου